Serine/threonine phosphatases and aquaporin-2 regulation in renal collecting duct - LeMaire, Sophia M. (Am J Physiol Renal Physiol, 2017)
Phosphorylation of the aquaporin-2 (AQP2) water channel at four COOH-terminal serines plays a central role in the regulation of water permeability of the renal collecting duct. The level of phosphorylation at these sites is determined by a balance between phosphorylation by protein kinases and dephosphorylation by phosphatases. The phosphatases that dephosphorylate AQP2 have not been identified. Here, we use large-scale data integration techniques to identify serine-threonine phosphatases likely to interact with AQP2 in renal collecting duct principal cells. As a first step, we have created a comprehensive list of 38 S/T phosphatase catalytic subunits present in the mammalian genome. Then we used Bayes’ theorem to integrate available information from large-scale data sets from proteomic and transcriptomic studies to rank the known S/T phosphatases with regard to the likelihood that they interact with AQP2 in renal collecting duct cells. To broaden the analysis, we have generated new proteomic data (LC-MS/MS) identifying 4538 distinct proteins including 22 S/T phosphatases in cytoplasmic fractions from native inner medullary collecting duct cells from rats. The official gene symbols corresponding to the top-ranked phosphatases (common names in parentheses) were: Ppp1cb (PP1-β), Ppm1g (PP2C), Ppp1ca (PP1-α), Ppp3ca (PP2-B or calcineurin), Ppp2ca (PP2A-α), Ppp1cc (PP1-γ), Ppp2cb (PP2A-β), Ppp6c (PP6C), and Ppp5c (PP5). This ranking correlates well with results of prior reductionist studies of ion and water channels in renal collecting duct cells.